Facts on Children's Lying: What Every Parent Needs to Know - Kate Fogarty (EDIS, 2009)
FAR0101, a 2-page transcript of the Family Album Radio Program broadcast by Kate Fogarty, describes research findings about lying in school-aged children and when parents should be concerned. Published by the UF Department of Family Youth and Community Sciences, March 2009.